2011
DOI: 10.1134/s0021364011010073
|View full text |Cite
|
Sign up to set email alerts
|

New high magnetic field phase of the frustrated S = 1/2 chain compound LiCuVO4

Abstract: Magnetization of the frustrated S = 1/2 chain compound LiCuVO4, focusing on high magnetic field phases, is reported. Besides a spin-flop transition and the transition from a planar spiral to a spin modulated structure observed recently, an additional transition was observed just below the saturation field. This newly observed magnetic phase is considered as a spin nematic phase, which was predicted theoretically but was not observed experimentally. The critical fields of this phase and its dM/dH curve are in g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
161
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(171 citation statements)
references
References 23 publications
9
161
0
1
Order By: Relevance
“…One of them expected just below saturation is the quadrupolar state of bound magnon pairs which is termed the spin-nematic state 19 . The J 1 -J 2 model has been used to describe various quasi-1D edge-sharing cuprates 12,[21][22][23][24][25][26][27][28][29] . Unfortunately, for many of the candidates for exhibiting multipolar phases, the involved AFM magnetic couplings and thus the saturation field are quite large, making it difficult to probe the multipolar phases.…”
mentioning
confidence: 99%
“…One of them expected just below saturation is the quadrupolar state of bound magnon pairs which is termed the spin-nematic state 19 . The J 1 -J 2 model has been used to describe various quasi-1D edge-sharing cuprates 12,[21][22][23][24][25][26][27][28][29] . Unfortunately, for many of the candidates for exhibiting multipolar phases, the involved AFM magnetic couplings and thus the saturation field are quite large, making it difficult to probe the multipolar phases.…”
mentioning
confidence: 99%
“…In a single crystal of LiCuVO 4 , a linear variation in magnetization has been observed just below the saturation at 1.3 K, which may be associated with a spin nematic order [30]. Such a linear variation is not discernible in Fig.…”
mentioning
confidence: 88%
“…It has been shown using large single crystals that LiCuVO 4 exhibits an incommensurate helical order at low fields [25][26][27][28][29], which may be a 3D analogue of the vector chirality order in the J 1 -J 2 chain, and a longitudinal SDW order at intermediate fields [26][27][28][29]. Furthermore, a spin nematic phase, a 3D analogue of the spin nematic state, has been suggested slightly below the saturation field of 44.4 T at H c, where the magnetization shows a linear field dependence [30]. However, the presence of the spin nematic phase is still unclear because of the high saturation field.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Note that exotic quantum phases such as spin-nematic, quadrupolar-order, and chiral-order phases are theoretically predicted in the CuO 2 ribbon chain systems [15][16][17] and a possible existence of the spin-nematic phase was experimentally reported in LiVCuO 4 . 18 We have studied the CuO 2 ribbon chain systems to clarify the multiferroic nature and search for exotic effects inherent to their quantum nature. The authors' group found that LiVCuO 4 2,4,6 and PbCuSO 4 (OH) 2 7,14 exhibit a direct transition from a paramagnetic and paraelectric phase to a multiferroic phase at transition temperature T N =2.4 K and 2.8 K, respectively.…”
Section: Introductionmentioning
confidence: 99%